2014
DOI: 10.1039/c4md00113c
|View full text |Cite
|
Sign up to set email alerts
|

Small-molecule phosphodiesterase probes: discovery of potent and selective CNS-penetrable quinazoline inhibitors of PDE1

Abstract: We describe the discovery of potent, selective, brain penetrable quinazoline inhibitors of PDE1 that represent valuable new tools for the dissection of related biological events.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
37
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 33 publications
(37 citation statements)
references
References 26 publications
0
37
0
Order By: Relevance
“…To measure the Ca 2+ /calmodulin-independent component of the PDE activity, we performed assays in the presence of EGTA and without added Ca 2+ /calmodulin. Addition of the PDE1 inhibitor PF-04822163 [ 43 ] to the assay mixture reduced the basal cGMP-hydrolyzing activity in the follicle lysates by ∼45%, but did not inhibit the increase in cGMP hydrolysis in response to LH ( Fig. 2 A).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…To measure the Ca 2+ /calmodulin-independent component of the PDE activity, we performed assays in the presence of EGTA and without added Ca 2+ /calmodulin. Addition of the PDE1 inhibitor PF-04822163 [ 43 ] to the assay mixture reduced the basal cGMP-hydrolyzing activity in the follicle lysates by ∼45%, but did not inhibit the increase in cGMP hydrolysis in response to LH ( Fig. 2 A).…”
Section: Resultsmentioning
confidence: 99%
“…2 A). PF-04822163 was used at 100 nM, a concentration that is specific for PDE1 [ 43 ]. These results indicated that Ca 2+ /calmodulin-independent PDE1 activity accounts for ∼45% of the basal cGMP-hydrolytic activity.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We tested a new PDE1 inhibitor, PF1 at 1 µM, a concentration chosen to be 10-times higher than its IC 50 for PDE1, 30-times lower than its IC 50 for PDE3, PDE4 or PDE9 and 10-times lower than its IC 50 for PDE5 (Humphrey et al, 2014). In this condition, PF1 totally abolished the Ca 2+ /CaM-stimulated cAMP-and cGMP-PDE activities measured in the lysates of the RASMCs, strongly supporting a PDE1 inhibitory action of PF1.…”
Section: Role Of Pde1 Pde5 and Pde9 In The Control Of Rasmcs Prolifementioning
confidence: 99%
“…Thus, the aim of the present study was to investigate the role of PDE1 in cyclic nucleotide compartmentation in synthetic VSMCs. We took advantage of a new quinazoline-based compound, PF-04471141 (named PF1), described as a potent inhibitor of PDE1 family (with IC 50 of 35-118 nM for human PDE1 subtypes) with more than 30-to 100-fold selectivity over other PDE families (Humphrey et al, 2014). To monitor intracellular cyclic nucleotide concentrations, fluorescence live cell imaging was conducted in cultured rat aortic SMCs (RASMCs) using Förster resonance energy transfer (FRET)-based sensors, an approach that has been widely used to evaluate the real-time dynamics of cAMP-or cGMP-dependent signals (Sprenger and Nikolaev, 2013).…”
mentioning
confidence: 99%